Strategies to improve survival outcomes of out-of-hospital cardiac arrest (OHCA) given a fixed budget: A simulation study. (April 2020) - Wei, Y.; Pek, P.P.; Doble, B.; Finkelstein, E.A.; Wah, W.; Ng, Y.Y.; Cheah, S.O.; Chia, M.Y.C.; Leong, B.S.H.; Gan, H.N.; Mao, D.R.H.; Tham, L.P.; et al.
Abstract: Background: Our study aimed to identify a strategy that maximizes survival upon hospital discharge or 30-days post out-of-hospital cardiac arrest (OHCA) in Singapore for fixed investments of S1, S5, or S10 million. Four strategies were compared: (1) no additional investment; (2) reducing response time via leasing of more ambulances; (3) increasing number of people trained in cardiopulmonary resuscitation (CPR); and (4) automated external defibrillators (AED). Methods: We estimated the effect of ambulance response time, bystander CPR and AED on survival based on Singapore's 2010–2015 OHCA registry data. We simulated the changes in ambulance response times and likelihood of (1) CPR and (2) AED usage as a function of their increased availability, which was then combined with the effect of each factor to determine the increase in survival for each strategy. Results: Survival given no additional investment was 4.03% (95% CI: 3.96%, 4.10%). The investments in ambulances, CPR training and AEDs for a given budget of S1M changed survival to 4.03% (95% CI: 3.96%, 4.10%), 4.04% (95% CI: 3.98%, 4.11%), and 4.44% (95% CI: 4.35%, 4.54%), respectively. This generated 0, 2 and 102 additional life years saved respectively. Given a budget of S5M or S10M, 509 or 886 additional life years could be saved, by investing in an additional 10, 000 or 20, 000 AEDs respectively. The strategies reached a saturation effect whereby improvement in survival was marginal when the budget was increased to ≥S5M for investment in ambulances and CPR training. Conclusions: Investing in AEDs had the most gain in survival.